Freeze-dried flexibility: a new morphology of labour, casualisation and value. (1st July 2011) - ,
Abstract : In recent decades, capitalist society has witnessed profound changes, including in the sphere of labour. Neoliberalism, the restructuring of production and economic expansion shaped through instantly-available, ''freeze-dried'' flexibility have led to far-reaching transformations in the world of work. As a result of this composite and heterogeneous set of transformations, there has been widespread speculation that we may be witnessing the end of the working class, or at least that labour has lost its central position in society. Recent history has been ruthless in relation to such (mis)constructions: the appearance of finitude has actually been part of a process whereby labour has been redesigned, leading to new modalities of labour and the emergence of a new morphology: a new way of being for labour, that coexists with and combines with its past (and still existing) arrangements. It seems that the more labour appears to dwindle, the broader and more diversified are the forms in which it can rise again (in this context it is irrelevant whether these new forms are more or less precarious or more or less provided with rights than those they replace). This article aims to pursue two of the key polysemic trends that are present in this framework: the casualisation of labour and the development of new forms of labour. It also addresses the implications of these interrelated connections for the law of value.